Asymmetric Total Synthesis of (–)-Galanthamine via Intramolecular Heck Reaction of Conjugated Diene - Choi, Juhee; Kim, Hyunseok; Park, Sangyun; Tae, Jinsung (Synlett, 2013)
Asymmetric total synthesis of (–)-galanthamine was accomplished starting from an epoxide. Intramolecular Heck reaction of a conjugated diene system was employed to construct the key quaternary carbon center. The cyclohexene-1,3-diol unit of (–)-galanthamine is derived from an optically active epoxy alkenol.
Keywords: epoxides; (–)-galanthamine; Heck reaction; metathesis; total synthesis